The Impact of Leverage on Firm Value By Mediation of Profitability (Case Study of Consumer Non-Cyclical Companies Listed on the Indonesia Stock Exchange for the 2014-2023 Period) - VIKI, Muhamad; MAHMUDI , Bambang; SURYANI, Emma (Journal of Governance, Taxation and Auditing, 2025)
This study aims to examine the effect of leverage on firm value using profitability as an intervening variable. In this study, firm value is measured by price-book value, leverage is measured by debt-equity ratio, and profitability is measured by return on assets. The population in this study is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2023 period, with a purposive sampling technique. The analytical methods used are the classical assumption test, partial test (t-test), path analysis, Sobel test and data testing was carried out using SPSS 23 software. The results of the hypothesis test, path analysis, and Sobel test indicate that: 1) Leverage has a negative effect on firm value. 2) Leverage has a negative effect on profitability. 3) Profitability has a positive effect on firm value. 4) Profitability is unable to mediate the effect of leverage on firm value. This research shows that signaling theory does not fully explain the relationship between leverage, profitability, and firm value in the non-cyclical consumer sector.